2017
DOI: 10.1186/s12971-017-0126-y
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of an exercise-counselling intervention to enhance smoking cessation outcomes: The Fit2Quit trial

Abstract: BackgroundIn the Fit2Quit randomised controlled trial, insufficiently-active adult cigarette smokers who contacted Quitline for support to quit smoking were randomised to usual Quitline support or to also receive ≤10 face-to-face and telephone exercise-support sessions delivered by trained exercise facilitators over the 24-week trial. This paper aims to determine the cost-effectiveness of an exercise-counselling intervention added to Quitline compared to Quitline alone in the Fit2Quit trial.MethodsWithin-trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…[ 28 ]. Higher per capita health gains for Māori vs non-Māori were identified (iv) Pharmacy-only sales and pharmacist counseling [ 32 ] (v) Promotion of the Quitline for smoking cessation [ 33 ] (vi) Promoting smartphone apps for smoking cessation [ 34 ] (vii) Two studies [ 35 , 36 ] on permitting ready access to e-cigarettes (albeit this has now largely occurred in NZ) Not cost-effective: Exercise counseling intervention to enhance smoking cessation [ 37 ] Comment: All the cost-saving studies detailed above capture CVD-related health benefits but also the benefits of preventing 14 other tobacco-related diseases. In one tobacco tax intervention study that identified how the QALYs gained were distributed, 16.6% were from CVD prevention and the majority were from chronic respiratory disease prevention (Table S6 in Blakely et al [ 29 ]) High body-mass index (BMI) 250 QALYs gained (from the weight-loss counseling intervention applied to 21.6% of the eligible population [ 38 ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 28 ]. Higher per capita health gains for Māori vs non-Māori were identified (iv) Pharmacy-only sales and pharmacist counseling [ 32 ] (v) Promotion of the Quitline for smoking cessation [ 33 ] (vi) Promoting smartphone apps for smoking cessation [ 34 ] (vii) Two studies [ 35 , 36 ] on permitting ready access to e-cigarettes (albeit this has now largely occurred in NZ) Not cost-effective: Exercise counseling intervention to enhance smoking cessation [ 37 ] Comment: All the cost-saving studies detailed above capture CVD-related health benefits but also the benefits of preventing 14 other tobacco-related diseases. In one tobacco tax intervention study that identified how the QALYs gained were distributed, 16.6% were from CVD prevention and the majority were from chronic respiratory disease prevention (Table S6 in Blakely et al [ 29 ]) High body-mass index (BMI) 250 QALYs gained (from the weight-loss counseling intervention applied to 21.6% of the eligible population [ 38 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Of note is that Table 2 refers to a program with an individual-level component, i.e., the mass media promotion of smartphone apps for weight loss [ 39 ]. See also the comment in Table 2 on physical activity interventions for weight loss Tobacco use Exercise counseling to enhance smoking cessation NZ$ 451,000 per QALY gained ($NZ 2012) (~ US$ 328,000 in 2018) This ICER was based on the 24-week follow-up data, using a discount rate of 3.5% [ 37 ], and is probably the most realistic ICER calculated in this study. As such, this ICER would not be considered cost-effective in the NZ context.…”
Section: Resultsmentioning
confidence: 99%
“…As it was only possible from the data to identify individuals who were non-smokers 1 year after previously describing themselves as current smokers, it was necessary to account for those smokers who attempted to quit but relapsed before being surveyed the following year. We estimate relatively high rates of quit attempts (15-25 quit attempts per 100 person-years), compared with the existing literature [104][105][106][107][108] (annual quit probabilities of around 4%). Full details are provided in Appendix 32, Smoking behaviour.…”
Section: Long-term Relapse and Spontaneous Quitsmentioning
confidence: 99%
“…In Leung et al (2017) and using Markov model in smokers facing increased risks of lung cancer and cardiovascular disease. The counselling intervention will only be cost-effective if adherence is in a range of 7 or more intervention calls, which then leads to the required a sufficient number of health gains for quitters.…”
Section: Literature Reviewmentioning
confidence: 99%